Laser-based Autonomous Navigation of Lawnmower - Abdul Rahim, Nur Adlina Shahirah; Shamsudin, Abu Ubaidah (Evolution in Electrical and Electronic Engineering, 2022)
Manual lawn mowing is a minor and difficult task that necessitates a long working hour in the sun and rain. The goal of this study is to create an autonomous lawn mower robot. This article shows the development process for a lawnmower robot, starting with 3D CAD hardware design in Solidworks, simulating the 3D cad design in Gazebo simulator, and incorporating autonomous navigation into the simulator using Robot Operating System. Gmapping, a well-known LIDAR-based SLAM method, is used to evaluate the reliability and accuracy of the autonomous lawnmower in the simulator for autonomous robot verification in terms of Simultaneous Localization and Mapping. The average accuracy of SLAM relative to ground truth is 98.4 percent for the x-axis and 98.86 percent for the y-axis.